Cross Talk Pathways Between Coagulation and Inflammation. Issue 9 (29th April 2016) - Foley, Jonathan H.; Conway, Edward M.
Abstract : Anatomic pathology studies performed over 150 years ago revealed that excessive activation of coagulation occurs in the setting of inflammation. However, it has taken over a century since these seminal observations were made to delineate the molecular mechanisms by which these systems interact and the extent to which they participate in the pathogenesis of multiple diseases. There is, in fact, extensive cross talk between coagulation and inflammation, whereby activation of one system may amplify activation of the other, a situation that, if unopposed, may result in tissue damage or even multiorgan failure. Characterizing the common triggers and pathways are key for the strategic design of effective therapeutic interventions. In this review, we highlight some of the key molecular interactions, some of which are already showing promise as therapeutic targets for inflammatory and thrombotic disorders.